New Social Horizons: Anxiety, Isolation, and Animal Crossing During the COVID-19 Pandemic - Lewis, Joanna E.; Trojovsky, Mia; Jameson, Molly M. (Frontiers in Virtual Reality, 2021)
Increased participation in activities has been associated with improved positive mental health outcomes. However, there is much debate regarding the net effects of video games on individuals. Typified as a socially isolating activity, many games inherently contain socialization within the environment with game generated characters or other players. Coinciding with the time of initial pandemic/quarantine period was the release of a popular socializing and life simulation game, Animal Crossing: New Horizons . We investigated whether participation in this game was related to emotional outcomes associated with pandemics, (e.g., loneliness and anxiety). The relationship between deleterious mental health and social gaming, amid a time of enforced reduction in socializing, would allow us to isolate the impact of the introduction of a social video game on improving quality of life for players of this game. Participants (n = 1053) were asked about their time spent playing video games via an online survey, their socialization in game-play, loneliness, and anxiety. We predicted that participants with higher levels of social interaction within the game would report less loneliness and anxiety. Utilizing multiple linear regression analyses, the research found that increased gaming and related activities was predictive of higher anxiety and somewhat related to increased loneliness. However, increased visits to another island was associated with lower levels of loneliness. As such, players may be utilizing gaming as a coping mechanism for anxiety. This research may inform generalized research regarding the influence that social games may have on feelings of loneliness and anxiety.